Produtos naturais no comportamento defensivo de Apis mellifera L. - Lomele, Renata Leonardo [UNESP]; Evangelista, Adriana [UNESP]; Ito, Mônica Miyuki [UNESP]; Ito, Érica Harue [UNESP]; Gomes, Silvia Maria Alves [UNESP]; Orsi, Ricardo Oliveira [UNESP] (Universidade Estadual de Maringa, 2010)
The goal was to investigate the influence of natural products such as lemongrass (Cymbopogon citratus), dried avocado leaves (Persea americana), coffee husk (Coffea arabica) and castor bean (Ricinus communis) in the defense of Apis mellifera, as well the effect of these products on the population development of the beehive. Defensive behavior was evaluated by time of first sting (TFS) and number of stingers (NS), and population development, by open brood area and operculated brood. It was observed that the treatment with smoke + seven castor beans presented significant increase in the TFS, for treatment without and with smoke. Regarding NS, it was verified that the treatments with smoke + seven castor bean and smoke + 20% coffee husk were different from the treatment without and with smoke. The other treatments did not differ significantly with respect to the use of smoke or its absence. The application of coffee husk and castor bean did not interfere in the development of the population, suggesting that these compounds were not toxic. It can be concluded that the use of castor bean and coffee husk in smoke may represent an important tool for the reduction of defensiveness, without promoting toxicity for A. mellifera.
Natural products in the defensive behaviour of Apis mellifera L.
Keywords: Beekeeping; Defensiveness; Management; Apis mellifera; Coffea arabica; Cymbopogon citratus; Hexapoda; Persea americana; Ricinus communis